Enhancing political trust through media diversity in post-pandemic China: policy insights for achieving sustainable development goals - Wei, Ming; Fu, Lingbo; Xiong, Chengyu; Fu, Hongpeng (Frontiers in Communication, 2025)
IntroductionPolitical trust is essential for achieving the United Nations’ Sustainable Development Goals (SDGs), especially in the context of new media’s impact during health crises. However, how political trust is influenced by media diversity still need further exploration, especially in the post-pandemic era. This study develops an integrated framework linking Diversity of Information (DI), Need for Cognition (NFC), Information Freedom Perception (IFP), Media Trust (MT), and Political Trust (PT) to examine these mechanisms in a post-pandemic context.MethodsAn online survey using validated measurement scales was conducted in China between October and December 2023. This study analyzed the 370 valid data through partial least squares structural equation modeling (PLS-SEM) to test the hypothesized paths among DI, NFC, IFP, MT, and PT. Cluster analysis and multi-group comparisons were then employed to identify heterogeneous user groups and to examine how the influence mechanisms vary across them.ResultsDI has a significant positive effect on PT and positively affects IFP and NFC. NFC, in turn, significantly impacts IFP, MT, and PT. Additionally, IFP significantly influences MT, and MT significantly influences PT. Cluster analysis identified three demographic groups: “Informed and Trusting,”“Isolated but Trusting,” and “Partially Informed and Skeptical.” Results indicate that the “Partially Informed and Skeptical” group perceives greater DI and less IFP compared to the “Isolated but Trusting” group.DiscussionThese findings underscore the critical role of media diversity in shaping residents’ trust in political and media institutions, particularly during crises. This study provides a long-term perspective on political trust in the post-pandemic era, which contributes to the SDGs by highlighting strategies to foster political trust through diverse and credible media environments, essential for sustainable governance.